Стратегія захисту інформації на основі математичного апарату теорії ігор - Фукс, М. А. (ХНУРЕ, 2023)
The aim of the work is to analyze the possibilities of the implementation of the mathematical model of a bimatrix game between the security administrator and attacker for determining an optimal security information strategy against possible attacks with a limited budget for the company. Different methodologies for implementing ISMS reflect the need to deploy and implement information security measures but do not present recommendations on how to conduct the selection. Therefore, CISO has to rely on its experience only. To assist him in defining the best strategy, the implementation of a bimatrix game was considered